Fabrication of Large-area Free-standing Ultrathin Polymer Films - Stadermann, Michael (J Vis Exp, 2015)
This procedure describes a method for the fabrication of large-area and ultrathin free-standing polymer films. Typically, ultrathin films are prepared using either sacrificial layers, which may damage the film or affect its mechanical properties, or they are made on freshly cleaved mica, a substrate that is difficult to scale. Further, the size of ultrathin film is typically limited to a few square millimeters. In this method, we modify a surface with a polyelectrolyte that alters the strength of adhesion between polymer and deposition substrate. The polyelectrolyte can be shown to remain on the wafer using spectroscopy, and a treated wafer can be used to produce multiple films, indicating that at best minimal amounts of the polyelectrolyte are added to the film. The process has thus far been shown to be limited in scalability only by the size of the coating equipment, and is expected to be readily scalable to industrial processes. In this study, the protocol for making the solutions, preparing the deposition surface, and producing the films is described.